2021
DOI: 10.1093/ndt/gfab347
|View full text |Cite
|
Sign up to set email alerts
|

Interim analysis of the COSA (COVID-19 patients treated with the Seraph® 100 Microbind® Affinity filter) registry

Abstract: Background The Seraph®100 Microbind Affinity Blood Filter® is a hemoperfusion device that is licensed for the reduction of pathogens, including several viruses, in the blood. It received Emergency Use Authorization (EUA) for the treatment of severe coronavirus disease 2019 (COVID-19) by the FDA. Several studies have shown that the blood viral load of SARS-CoV-2 correlates with adverse outcomes and removal of the nucleocapsid of the SARS-CoV-2 virus by the Seraph®100 has been recently demonstr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
1
19
1
1
Order By: Relevance
“…Therefore, other renal replacement therapy modalities could not be investigated in this study. However, outside of this investigation the device has been used in the setting of prolonged intermittent renal replacement therapy [29], continues kidney replacement therapy [31] and standalone hemoperfusion [32].…”
Section: Study Limitationsmentioning
confidence: 99%
“…Therefore, other renal replacement therapy modalities could not be investigated in this study. However, outside of this investigation the device has been used in the setting of prolonged intermittent renal replacement therapy [29], continues kidney replacement therapy [31] and standalone hemoperfusion [32].…”
Section: Study Limitationsmentioning
confidence: 99%
“…Notably, this is in the context of a critically ill patient population and treatments that lasted for a prolonged period of time (median of 13 hr). This low rate of SAEs is consistent with the only other large series of Seraph 100 in patients with COVID 19, which reported nine adverse events over the course of 102 treatments ( 20 ). Most of these events were circuit failure, and none were considered serious.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published interim analysis of a multicenter observational study in 12 hospitals monitoring 102 treatment sessions in 82 patients confirmed that the treatment was well tolerated. Mortality was correlated with late initiation of the treatment as well as with bacterial super-infection ( Schmidt et al, 2022 ). Although the efficacy of this approach has yet to be consistently demonstrated, current data suggest that it can be deployed as an adjunct measure until directed pharmacologic countermeasures are available ( Chitty et al, 2022 ).…”
Section: Therapeutic Potential Of Platelet-derived Ev Depletion Durin...mentioning
confidence: 99%